ANALYSIS OF FACTORS INFLUENCING CAPITAL STRUCTURE, DIVIDEND POLICY, TOTAL ASSETS ON FIRM VALUE IN THE BANKING SECTOR ON THE INDONESIA STOCK EXCHANGE (IDX) - Hutabarat, Oktavia Arisanti; Tarigan, Jelli; Putri, Tantri Octora Dwi Syah; Miraza, Zuwina (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
In the banking sector, company value plays an essential role in the success of company management. Therefore, efforts must be made to improve several aspects of the banking industry. Key areas for improvement include capital structure, dividend policy, and total assets. The objective of this research is to determine whether there is an influence of capital structure, dividend policy, and total assets on company value. This research adopts a quantitative method using secondary data sourced from the Indonesian Stock Exchange (BEI), with a total of 35 samples. The results of this research are shown in the R-squared value, which is 82.9%. This indicates that the variables X1 (capital structure), X2 (dividend policy), and X3 (total assets) significantly influence company value.